Delaying Anticancer Drug Delivery by Self‐Assembly and Branching Effects of Minimalist Dendron–Drug Conjugates. Issue 41 (11th June 2019) - Correard, Florian; Roy, Myriam; Terrasson, Vincent; Braguer, Diane; Estève, Marie‐Anne; Gingras, Marc
Abstract: Invited for the cover of this issue are the groups of Marc Gingras and Diane Braguer and their colleagues at Aix‐Marseille Université. The image depicts the anticancer activity (boxing glove) of PEG‐dendrons conjugated to paclitaxel (yellow) against cancer cells (red cells). Read the full text of the article at 10.1002/chem.201801092 . Abstract : " This work originated from a nice collaboration between pharmacists and chemists at Aix‐Marseille Université working at the interface of dendrimers and supramolecular chemistry, materials science, anticancer drug delivery, and nanomedicine " Read more about the story behind the cover in the Cover Profile and about the research itself on page 9586 ff. (DOI:10.1002/chem.201801092 ).